Non-synaptic Plasticity in Leech Touch Cells - Meiser, Sonja; Ashida, Go; Kretzberg, Jutta (Frontiers in Physiology, 2019)
The role of Na+/K+-pumps in activity-dependent synaptic plasticity has been described in both vertebrates and invertebrates. Here we provide evidence that the Na+/K+-pump is also involved in activity-dependent non-synaptic cellular plasticity in leech sensory neurons. We show that the resting membrane potential of T cells hyperpolarizes in response to repeated somatic current injection, while at the same time their spike count and the input resistance increase. Our Hodgkin-Huxley-type neuron model, adjusted to physiological T cell properties, suggests that repetitive action potential discharges lead to increased Na+/K+-pump activity, which then hyperpolarizes the resting membrane potential. In consequence, a slow, non-inactivating current decreases, which is presumably mediated by voltage-dependent, low-threshold potassium channels. Closing of these putative M-type channels due to hyperpolarization of the resting potential increases the input resistance of the cell, leading to a larger number of spikes. By this mechanism, the response behavior switches from rapidly to slowly adapting spiking. These changes in spiking behavior also effect other T cells on the same side of the ganglion, which are connected via a combination of electrical and chemical synapses. An increased spike count in the presynaptic T cell results in larger postsynaptic responses in the other T cells. However, when the number of elicited presynaptic spikes is kept constant, the postsynaptic response does not change. These results suggest that T cells change their responses in an activity-dependent manner through non-synaptic rather than synaptic plasticity. These changes might act as a gain-control mechanism. Depending on the previous activity, this gain could scale the relative impacts of synaptic inputs from other mechanoreceptors, versus the spike responses to tactile skin stimulation. This multi-tasking ability, and its flexible adaptation to previous activity, might make the T cell a key player in a preparatory network, enabling the leech to perform fast behavioral reactions to skin stimulation.